ANALISIS FRAMING OBJEKTIFIKASI PEREMPUAN PADA PEMBERITAAN KASUS PERSELINGKUHAN DI PORTAL BERITA INDOZONE.ID DAN TRIBUNNEWS.COM PERIODE FEBRUARI HINGGA MARET 2021 - Dwi Prasetyo Wahyuningtyas; Aulia Rahmawati (Linimasa : Jurnal Ilmu Komunikasi, 2023)
Regardless the role of women as perpetrators or victims in the society cases, the mass media often portrays women as the parties who always cause problems. This study aims to determine the objectification and representation of women in the news framing in the news of Nissa Sabyan has an affair with Ayus Sabyan on the news portal Indozone.id and Tribunnews.com for the period February to March 2021. The analysis will use the framing analysis method from Pan & Kosicki on eighteen corpus. The results of the study indicate that there are similarities in the news themes presented on the two news portals, that female actors have a greater responsibility for the occurrence of infidelity in relationship. However, there are differences in conveying the news, where Indozone.id tends to put Nissa Sabyan as pelakor (perebut lelaki orang) or a label for woman who flirts to men who already have a partner. While Tribunnews.com portrays Ayus with good images. The objectification of women on the two news portals is shown through the choice of words such as “tidak harus cantik”, “gatel”, and “wanita cantik”which indicate there are standart to categorize women. Furthermore, the mass media choose to compare Nissa Sabyan and Ririe Fairus by using the words “lebih memilih”, “dibandingkan”, “daripada” for Ayus statement to end his marriage status. Rather than doing that, the mass media should comparing infidelity and marriage by giving narations that Ayus wants to continuou his relationship with Nissa Sabyan than to keep his marriage with Ririe Fairus.